Konsep Pendidikan Rasulullah Sebagai Solusi Masalah Rendahnya Sumber Daya Manusia di Indonesia - Usan Usan (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STITNU Al-Farabi Pangandaran, 2022)
This paper aims to examine efforts to improve the quality of human resources in education in Indonesia which is very worrying where the quality rating when compared to other countries is in a lagging position. The research method used is a qualitative approach with descriptive analysis sourced from secondary data through scientific writings on Islamic education. The results of this study found that the phenomenon of the low quality of human resources in education in Indonesia can be taken seriously by immediately looking for solutions that can increase the quality of this nation's education and apply them as a whole seriously and guided by the best role models in mind. The Prophet who has been proven to give birth to the best generations of people through various concepts and learning.